2000
DOI: 10.1055/s-2000-9808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β2-Glycoprotein I and Monoclonal Anticardiolipin Antibodies on Extrinsic Fibrinolysis

Abstract: Antiphospholipid antibodies (aPLs) are associated with an increased incidence of thrombosis, but the mechanisms responsible for thrombosis are unclear. The present study investigated the effect of both beta2-glycoprotein I (beta2-GPI) and aPLs on the activity of extrinsic fibrinolysis. The remaining tissue-plasminogen activator (t-PA) of the sample consisting of beta2-GPI, two-chain recombinant t-PA, plasminogen activator inhibitor (PAI) -1 was measured by a chromogenic assay using synthetic substrate S-2251, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
0
21
0
2
Order By: Relevance
“…In 1999, Ieko et al (34,35) reported that ␤ 2 GPI exerted a dose-dependent enhancement of t-PA activity in the presence of PAI-1, and that addition of EY1C8 patient-derived monoclonal aCL reduced t-PA activity by ϳ45% in a mixture of t-PA (3.6 U/ml), PAI-1 (7.1 ng/ml), and ␤2GPI (3.8 M). In 2000, Cugno et al (36) showed that of 39 patients with primary APS, three had high titers of IgG Ab against t-PA, and four had high titers of Ab against fibrin-bound t-PA, which is the physiologically active form of t-PA.…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, Ieko et al (34,35) reported that ␤ 2 GPI exerted a dose-dependent enhancement of t-PA activity in the presence of PAI-1, and that addition of EY1C8 patient-derived monoclonal aCL reduced t-PA activity by ϳ45% in a mixture of t-PA (3.6 U/ml), PAI-1 (7.1 ng/ml), and ␤2GPI (3.8 M). In 2000, Cugno et al (36) showed that of 39 patients with primary APS, three had high titers of IgG Ab against t-PA, and four had high titers of Ab against fibrin-bound t-PA, which is the physiologically active form of t-PA.…”
Section: Discussionmentioning
confidence: 99%
“…These include the activation of endothelial cells, oxidant-mediated vascular endothelium lesions, interference with or modulation of the phospholipid-binding proteins regulating hemostasis, and mechanisms similar to heparin-induced thrombocytopenia. 1 Reduced fibrinolytic activity has also been described in patients with APS, and may be responsible for thrombotic events, [2][3][4][5] and antibodies directed against tissue-type plasminogen activator (tPA) might lead to a hypofibrinolytic state. Our previous studies have shown that an association between anti-tPA antibodies and thrombosis seems to be a peculiarity of APS because normal plasma anti-tPA antibody levels were found in 100 patients with a history of deep vein thrombosis (DVT) without APS, 6 but high levels in 3 of 39 patients with primary APS who had a history of thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…They appear to interfere with a range of normal cell surface hemostatic mechanisms by targeting coagulation factors, natural anticoagulants, oxidized low-density lipoproteins, CD36, and fibrinolytic proteins. [4][5][6][7][15][16][17][18][19] Emerging evidence suggests that plasma hypofibrinolysis is a risk factor for venous thrombosis, 20 and that fibrinolysis might be impaired in APS due to increased fibrinolytic inhibitor (plasminogen activator inhibitor type-1) activity. 21 Annexin A2 (A2) is a profibrinolytic receptor that binds both plasminogen and its activator, tissue plasminogen activator (tPA), functioning as a cofactor for plasmin generation, and localizing fibrinolytic activity to the EC surface.…”
Section: Introductionmentioning
confidence: 99%